Технологічні аспекти та технічні засоби виробництва біогазу - Куценко, Юрій Миколайович; Куценко, Юрий Николаевич; Kutsenko, Yurii (ТДАТУ, 2014)
UK: Проведено аналіз основних джерел біомаси для виробництва біогазу. RU: Проведен анализ основных источников биомассы для производства биогаза. EN: The analysis of main sources of biomass for biogas production, processes of the production of biogas for various agricultural enterprises are considered in a paper.
Технологические аспекты и технические средства производства биогаза
Technological aspects and technical means of the biogas production
Keywords: біоенергоконверсія; біогазові установки; тверді побутові відходи; агропромислові підприємства